Symbiont Chloroplasts Remain Active During Bleaching-Like Response Induced by Thermal Stress in Collozoum pelagicum (Collodaria, Retaria) - Villar, Emilie; Dani, Vincent; Bigeard, Estelle; Linhart, Tatiana; Mendez-Sandin, Miguel; Bachy, Charles; Six, Christophe; Lombard, Fabien; Sabourault, Cécile; Not, Fabrice (Frontiers in Marine Science, 2018)
Collodaria (Retaria) are important contributors to planktonic communities and biogeochemical processes (e.g. the biologic pump) in oligotrophic oceans. Similarly to corals, Collodaria live in symbiosis with dinoflagellate algae, a relationship that is thought to explain partly their ecological success. In the context of global change, the robustness of the symbiotic interaction and potential subsequent bleaching events are of primary interest for oceanic ecosystems functioning. In the present study, we compared the ultrastructure, morphology, symbiont density, photosynthetic capacities and respiration rates of colonial Collodaria exposed to a range of temperatures corresponding to natural conditions (21°C), moderate (25°C) and high (28°C) thermal stress. We showed that symbiont density immediately decreased when temperature rose to 25°C, while the overall Collodaria holobiont metabolic activity increased. When temperature reached 28°C, the holobiont respiration nearly stopped and the host morphological structure was largely damaged, as if the host tolerance threshold has been crossed. Over the course of the experiment, the photosynthetic capacities of remaining algal symbionts were stable, chloroplasts being the last degraded organelles in the microalgae. These results contribute to a better characterization and understanding of temperature-induced bleaching processes in planktonic photosymbioses.